2020
DOI: 10.1002/jmri.27339
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Nodal Matting on MRI in Nasopharyngeal Carcinoma Patients

Abstract: Background: Nodal (N) stage is one of the most important predictors for distant metastasis in nasopharyngeal carcinoma (NPC) patients. It may ignore potentially useful nodal features, such as nodal matting (three or more lymph nodes abutting together with the absence of intervening fat planes). Purpose: To explore the prognostic value of nodal matting in NPC patients and construct a nomogram with nodal matting for predicting distant metastasis-free survival (DMFS). Study type: Retrospective. Population: In all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…More and more studies have found that the presence of nodal metastases is one of the key factors that predict patients at risk of distant metastases. These studies have gone further to investigate the prognostic values of nodal characteristics in detail [ 42 46 ]. Necrosis is easily observed in metastatic nodes from NPC but very rarely in primary tumour (about 2%) on the pre-treatment staging MRI [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies have found that the presence of nodal metastases is one of the key factors that predict patients at risk of distant metastases. These studies have gone further to investigate the prognostic values of nodal characteristics in detail [ 42 46 ]. Necrosis is easily observed in metastatic nodes from NPC but very rarely in primary tumour (about 2%) on the pre-treatment staging MRI [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies have found that the presence of nodal metastases is one of the key factors that predict patients at risk of distant metastases. These studies have gone further to investigate the prognostic values of nodal characteristics in detail [42][43][44][45][46]. Necrosis is easily observed in metastatic nodes from NPC but very rarely in primary tumour (about 2%) on the pre-treatment staging MRI [34].…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC) is a common malignant tumor with unbalanced geographic distribution, and It is often diagnosed in Southern China, Southeast Asia and North Africa 1 . Unlike other head and neck cancers, radiation therapy (RT) is the mainstay of treatment for non-metastatic NPC given its deep-seated anatomical location and high sensitivity to radiation.…”
Section: Introductionmentioning
confidence: 99%